Is there a positive incentive effect from privatizing social security : evidence from Latin America - Packard, Truman (Policy research working paper, 2001)
Introducing individual retirement accounts has a positive incentive effect that increases the share of the economically active population contributing to the reformed pension system. But this effect occurs only gradually as employers and workers become familiar with the new set of social insurance institutions put in place by reform